Screening Activities of Crude Extracts Produced Halodule sp. Seagrass-Associated Fungus - Safwan, Safwan; Ridwan, Sucilawaty; Musyarrafah, Musyarrafah; Wijayanti, Rina (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Secondary metabolites from marine microorganisms, including marine-derived fungi, have consented to developing guide bioactive compounds. Marine-derived fungi were reported to be associated with various habitats, including seagrasses. The seagrass-associated fungus from the Indonesian marine area is still poorly unexplored. This study was presented to screen for the antimicrobial and antioxidant activity of crude extracts produced by fungi associated with Seagrass (Halodule sp.) collected from Indonesia. Fresh samples were collected and kept fresh until they arrived in the Laboratory and immediately planted on Potato Dextrose Agar (PDA) Sea Salt media. Ten fungi were isolated and purified using a Malt Extract Agar (MEA) medium and subjected to fermentation treatment for 30 days using solid rice media. The compounds produced were collected by soaking directly using ethyl acetate (EA) for one hour while stirring mechanically. Evaporation of EA was carried out to obtain crude extracts. Each crude extract was subjected to antibacterial and antioxidant activities using the agar diffusion and DPPH methods, respectively. Reverse-phase Thin-Layer Chromatography (TLC) was used to observe the compound profile. The results of the activity test showed that two crude extracts from fungi with the code A.10.4 and B.5.1 had both activities, antibacterial (potent inhibition at 50% concentration and antioxidant (IC50 of 90.23 and 88.29 ppm, respectively). Another crude extract with the fungi code B.1.1 showed strong antioxidant activity (IC50 of 81.31 ppm) without antimicrobial activity. TLC results show different compound profiles from each crude extract and quite a good separation.